Integrating mobile-assisted language learning (MALL) in teaching EFL: A study on senior high school teachers in Indonesia - Erfan Sabani; Fardini Sabilah; Rina Wahyu Setyaningrum (Universitas Muhammadiyah Malang, 2025)
The use of technology, particularly mobile devices, has revolutionized learning by providing access to diverse digital materials, promoting lifelong learning, and facilitating cooperative knowledge exchange. Teachers' lack of digital skills and students' excessive mobile phone use pose obstacles to effective technology integration, leading to distractions and poor academic performance. Despite these challenges, Mobile Assisted Language Learning (MALL) has shown promise in promoting interactive English language exercises and improving language proficiency by offering flexible learning environments. This study employed a multiple case study approach to identify the digital learning platforms used by 5 teachers in teaching English from 5 different senior high schools in eastern part of East Java province. The interview data was analyzed using thematic analysis and member checking was employed to ensure data credibility. From the findings, some of the digital platforms that can be used in learning teaching receptive skills and productive skills. Despite the availability of digital tools, several challenges were identified include teachers' unfamiliarity with digital platforms, big size class, and limited supporting equipment. To address the challenges, teachers adopted strategies such as participating in MGMP activities, seminars, webinars and implementing collaborative/group learning and using multimedia laboratories, free platforms and the internet (hotspots). The findings suggest that with proper support and training, the integration of digital platforms can enhance engagement and improve English language outcomes.